Novel cobalt-based brazing filler metal and preparation method and application thereof

By optimizing the alloy element ratio and preparation process of cobalt-based solder, Co×NiCrFe(Si,B) cobalt-based solder is formed, which solves the problem that the existing high-temperature cobalt-based solder cannot meet the connection requirements of cemented carbide and titanium in high-thrust-weight engines, and achieves the improvement of high-temperature performance, wetting and mechanical properties.

CN119609452AActive Publication Date: 2025-03-14SHANGHAI UNIV OF ENG SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411547756.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-14
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing high-temperature cobalt-based solder cannot meet the connection requirements of cemented carbide and titanium in high-thrust-weight engines, especially at high temperatures, which lack sufficient corrosion resistance, wetting and mechanical properties.

Method used

By optimizing the alloy element ratio of the cobalt-based solder, the content of nickel, chromium, iron, boron, manganese, silicon and rare earth elements is increased to form Co×NiCrFe(Si,B) cobalt-based solder, and it is prepared using a high-vacuum non-consumable arc melting furnace.

Benefits of technology

It improves the high-temperature performance, oxidation resistance, wetting and mechanical properties of cobalt-based brazing, meets the brazing connection requirements of high-temperature different metal materials, and provides good compressive strength and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609452A_ABST
    Figure CN119609452A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high-temperature alloy connection, and particularly discloses novel cobalt-based brazing filler metal for high-temperature dissimilar metal connection and a preparation method and application of the novel cobalt-based brazing filler metal. The cobalt-based brazing filler metal is prepared from, by weight, 30%-70% of Co, 14%-27% of Ni, 11%-20% of Cr, 3%-6.5% of Fe, 1%-1.5% of Mn, 3%-6% of Si, 2%-4% of B, 0.3%-0.5% of Sc, 0.2%-0.4% of Y and the balance inevitable impurities. The melting point of the cobalt-based brazing filler metal ranges from 950 DEG C to 1100 DEG C, and the cobalt-based brazing filler metal is suitable for being used in the high-temperature environment of 600 DEG The method focuses on the refining process and performance evaluation of the Co * NiCrFe (Si, B) cobalt-based brazing filler metal, the content of the Co element is systematically adjusted, the brazing strength of the brazing filler metal is guaranteed, meanwhile, the wettability of the brazing filler metal is improved, composition segregation is reduced, and the process requirement for brazing connection of high-temperature dissimilar metal materials can be fully met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-temperature alloy connection, and in particular to a novel cobalt-based brazing filler metal for high-temperature alloy connection, a preparation method and application thereof. The brazing filler metal is suitable for laser brazing of high-temperature alloys. Background Art

[0002] With the development of high thrust-to-weight ratio aircraft engines, some important engine parts adopt complex structures of titanium shell and hard alloy on local contact surface, so as to meet the demand of new generation of high thrust-to-weight ratio engines for new lightweight and high temperature resistant structural materials and the performance requirements of high hardness, high strength and high temperature resistance of connection parts. For the connection method of complex and precise dual alloy structures, brazing is currently the most commonly used method.

[0003] The selection of brazing filler metal is particularly critical during the brazing process. During brazing, the brazing filler metal wets the base metal and uses capillary action to achieve interatomic bonding with the base metal. Cobalt-based brazing material is generally based on Co as the matrix, with alloy elements such as Ni, Cr, and W added, and B and Si as melting-reducing elements. Cobalt has a high melting point, and both Co-Cr and Co-Ni can form solid solutions. This brazing filler metal has excellent comprehensive mechanical properties. However, with the rapid development of high thrust-to-weight ratio engines in recent years, the existing high-temperature brazing fillers can no longer meet current needs. Therefore, it is necessary to develop new high-temperature brazing fillers with better performance to solve the connection problem between cemented carbide and titanium in high thrust-to-weight ratio engines. Summary of the invention

[0004] The purpose of the present invention is to provide a new cobalt-based brazing filler metal for high-temperature alloy connection and its preparation method and application to solve the above problems. Based on the performance of the existing cobalt-based brazing filler metal, the present invention proportions the alloy elements of the cobalt-based brazing filler metal according to the performance influence between the alloy elements, and obtains a cobalt-based brazing filler metal with excellent performance and suitable melting point. The brazing filler metal has the advantages of high temperature resistance, corrosion resistance, good wettability, good mechanical properties, etc., and can meet the current high thrust-to-weight ratio engine demand for high-temperature brazing filler metal.

[0005] In order to achieve the above object, the specific technical solution adopted by the present invention is as follows:

[0006] In a first aspect, the present invention provides a novel cobalt-based solder, which comprises, by weight percentage (total 100wt%), 30-70% Co, 14-27% Ni, 11-20% Cr, 3-6.5% Fe, 1-1.5% Mn, 3-6% Si, 2-4% B, 0.3-0.5% Sc, 0.2-0.4% Y, and the remainder being unavoidable impurities (a small amount of S and P).

[0007] The Co×NiCrFe(Si, B) cobalt-based solder of the present invention is based on cobalt, has relatively high contents of nickel and chromium, and contains an appropriate amount of iron and a small amount of boron, manganese and silicon. The solder of the present invention is used at high temperature. Chromium is an indispensable element in high temperature alloys, which improves the high temperature performance and oxidation resistance of cobalt-based solder. Nickel is the main forming element of austenite and the forming element of the strengthening phase γ′. It mainly segregates into the γ′ phase to stabilize the γ′ phase, and the γ′ phase is the most important strengthening phase in high temperature alloys, which improves the strength of the solder. The role of iron in the solder is to strengthen the γ phase, which plays a role of dispersion strengthening and precipitation strengthening. Boron makes the grain boundary segregate, reduces grain boundary defects, improves the grain boundary strength, can significantly change the grain boundary shape, improves the plasticity of the cobalt-based alloy, and improves the wettability and deoxidation of the solder. The addition of silicon can reduce the melting point of the solder. The addition of rare earth elements yttrium and scandium can significantly improve the high temperature strength, structural stability, welding performance and corrosion resistance of the solder, and can reduce the embrittlement phenomenon that is easy to occur when working for a long time at high temperature. The cobalt-based solder of the present invention can be used in high temperature, high pressure, corrosion resistance and other environments after welding.

[0008] In one embodiment of the present invention, the solder composition is, measured by weight percentage, Co 35%, Ni 27%, Cr 20%, Fe 6.5%, Mn 1.5%, Si 6%, B 3%, Sc 0.5%, Y 0.4%, and the remainder is inevitable impurities.

[0009] In one embodiment of the present invention, the solder composition is, by weight percentage, Co 50%, Ni 20%, Cr 15%, Fe 6%, Mn 1%, Si 5%, B 2%, Sc 0.5%, Y 0.4%, and the remainder is inevitable impurities.

[0010] In one embodiment of the present invention, the solder composition is, by weight percentage, Co 65%, Ni 14%, Cr 11%, Fe 3%, Mn 1%, Si 3%, B 2%, Sc 0.5%, Y 0.4%, and the remainder is inevitable impurities.

[0011] In a second aspect, the present invention provides a method for preparing the novel cobalt-based solder, comprising the following steps:

[0012] (1) Batching: Weigh the raw materials of each component to be smelted according to the mass percentage of the solder;

[0013] (2) Melting: The weighed raw materials are melted at high temperature in a high vacuum non-consumable arc melting furnace. After the melting is completed, the raw materials are cooled to room temperature and sampled to obtain an alloy ingot of the brazing material;

[0014] (3) Cutting: Cut the alloy mother ingot into the required shape and size by wire cutting method.

[0015] Furthermore, in step (1), the raw materials of each component are particles with a purity greater than 99.99%.

[0016] Furthermore, in step (2), the non-consumable arc melting furnace is evacuated to below -4 Pa before smelting, and then filled with argon gas with a purity of 99.99% until the pressure reaches -0.05 MPa.

[0017] Furthermore, in step (2), the high temperature smelting process is: 1500-1600°C for 3 min, 1400-1500°C for 3 min, 1300-1400°C for 3 min, during which an electromagnetic stirrer is turned on for stirring, the current is controlled at 400-600A, and pouring is performed at 1400°C.

[0018] In a third aspect, the present invention provides an application of the novel cobalt-based brazing filler metal, which can be used for brazing dissimilar high-temperature alloy materials of cemented carbide and titanium or cemented carbide and steel, and the brazing temperature (melting point) is 950°C to 1100°C.

[0019] Furthermore, the brazing connection method is as follows: the brazing material is placed between two base materials to be welded, and after being fixed with a clamp, the sample is laser brazed, the laser power is 1400W, the laser scanning speed is 0.012m / s, the defocus amount is -0.8mm, the protective gas is argon (99.99%), and the gas flow rate is 23L / min.

[0020] The present invention has the following beneficial effects:

[0021] 1. The present invention improves the wettability of the solder and reduces component segregation while ensuring the solder's brazing strength and hardness, and can fully meet the process requirements of high-temperature dissimilar metal materials brazing connection.

[0022] 2. The brazing connection using the brazing filler metal of the present invention has good compressive strength and corrosion resistance, and has a better high-temperature service temperature (600°C to 800°C), which can effectively solve the connection and repair problems of high-temperature alloy parts in harsh environments and has important application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 : Appearance of Co×NiCrFe(Si,B) cobalt-based ingots prepared in Examples 1-3. In the figure: (a) front side of A1 solder; (b) front side of A2 solder; (c) front side of A3 solder; (d) back side of A1 solder; (e) back side of A2 solder; (f) back side of A3 solder.

[0024] Figure 2: XRD pattern of Co×NiCrFe(Si,B) cobalt-based solder prepared in Examples 1-3.

[0025] Figure 3 : DSC curves of Co×NiCrFe(Si,B) cobalt-based solders prepared in Examples 1-3.

[0026] Figure 4 : The spreading area of ​​the Co×NiCrFe(Si,B) cobalt-based brazing filler metal prepared in Examples 1-3 on the parent materials (titanium and cemented carbide).

[0027] Figure 5 : Microhardness of Co×NiCrFe(Si,B) cobalt-based solder prepared in Examples 1-3. In the figure, (a) A1 group cobalt-based solder; (b) A2 group cobalt-based solder; (c) A3 group cobalt-based solder. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and specific examples.

[0029] Example 1

[0030] This embodiment provides a novel cobalt-based solder A2, which is composed of Co35%, Ni 27%, Cr 20%, Fe 6.5%, Mn 1.5%, Si 6%, B 3%, Sc 0.5%, Y 0.4%, and a small amount of S and P impurities, and the sum of the mass percentages of the components is 100wt%. The novel cobalt-based solder is prepared by the following method:

[0031] (1) Ingredients: According to the mass percentage of the solder, use a high-precision electronic balance to accurately weigh the raw materials of each component to be smelted, and the error is controlled within ±5mg to ensure the accuracy of the test. The total weight of the raw materials is 200g, and the raw materials of each component are particles with a purity greater than 99.99%.

[0032] (2) Melting: A high vacuum non-consumable arc melting furnace (model DHL500) was evacuated to below -4 Pa, and then filled with argon gas with a purity of 99.99% until the pressure mark reached -0.05 MPa; the weighed raw materials were placed in the melting furnace and melted according to the following process: 1500-1600°C for 3 min, 1400-1500°C for 3 min, and 1300-1400°C for 3 min, during which an electromagnetic stirrer was turned on for stirring, and the current was controlled at 400-600A. The casting was performed at 1400°C. After the melting was completed, the raw materials were cooled to room temperature and sampled to obtain an alloy ingot of the solder.

[0033] (3) Cutting: Cut the alloy mother ingot into the required solder blocks by wire cutting method.

[0034] Example 2

[0035] This embodiment provides a novel cobalt-based solder A2, which, by weight percentage, comprises Co50%, Ni 20%, Cr 15%, Fe 6%, Mn 1%, Si 5%, B 2%, Sc 0.5%, Y 0.4%, and a small amount of S and P impurities, and the sum of the mass percentages of the components is 100wt%. The preparation method of the novel cobalt-based solder is the same as that of Embodiment 1 except for the weight of the raw materials.

[0036] Example 3

[0037] This embodiment provides a novel cobalt-based solder A3, which comprises, by weight percentage, Co65%, Ni 14%, Cr 11%, Fe 3%, Mn 1%, Si 3%, B 2%, Sc 0.5%, Y 0.4%, and a small amount of S and P impurities, and the sum of the mass percentages of the components is 100wt%. The preparation method of the novel cobalt-based solder is the same as that of Embodiment 1 except for the weight of the raw materials.

[0038] The solders prepared in Examples 1-3 were characterized and tested for performance, as follows:

[0039] 1. Carry out metallographic observation on the solder block. The results are as follows: Figure 1 As shown, the metallographic phases of the solders of Examples 1-3 are dense without obvious defects, and compared with Examples 1 and 2, the surface morphology of the cobalt-based ingot of Example 3 is more uniform.

[0040] 2. XRD test was performed on the solder block. The results Figure 2 As shown, the Co×NiCrFe(Si,B) cobalt-based solders of Examples 1-3 mainly contain Co, Cr, FeNi3 and Cr2B phases.

[0041] 3. Perform DSC curve test on the solder block, the results are as follows Figure 3 As shown, the melting point of the solder block is A1<A2<A3; when the Co content is 35wt.%, the melting range of the cobalt-based solder is 60.6℃; when the Co content increases to 50wt.%, the melting range of the cobalt-based solder is 102.8℃; when the Co content increases to 65wt.%, the melting range of the cobalt-based solder is reduced to 80.2℃. The solders of Examples 1-3 all have smaller melting ranges. The reduction of the melting range can improve the fluidity of the cobalt-based solder during brazing, and it is not easy to cause component segregation.

[0042] 4. Carry out wettability test on solder block. The results are as follows: Figure 4 As shown: Example 1 The spreading area of ​​the brazing material on the cemented carbide is 76.38 mm 2 , the spreading area of ​​titanium is 70.32mm2 ; Example 2 The spreading area of ​​the brazing material on the cemented carbide is 91.86mm 2 , the spreading area of ​​titanium is 82.28mm 2 ; Example 3 The spreading area of ​​the brazing material on the cemented carbide is 100.58mm 2 , the spreading area of ​​titanium is 83.71mm 2 The three groups of solders all have good wettability, and Example 3 has the best wetting effect.

[0043] 5. Perform microhardness test on the solder block. The results are as follows: Figure 5 As shown, when the Co content is 35wt.%, the microhardness is 273.53HV; when the Co content increases to 50wt.%, the microhardness increases to 284.43HV; however, when the Co content continues to increase to 65wt.%, the microhardness decreases to 229.03HV. All three groups of solders have good hardness, and Example 2 has the highest hardness.

[0044] Application Example 1

[0045] The brazing material block A1 prepared in Example 1 is used to perform brazing between dissimilar metals, and the base materials to be welded are cemented carbide (WC-20Co) and titanium (TA2). The specific brazing method is as follows:

[0046] Before welding, the cemented carbide (WC-20Co) and titanium (TA2) samples were polished with 800 sandpaper on the surface to be welded, and ultrasonically cleaned in acetone for 15 minutes to remove oil stains on the surface of the samples to be welded; the cut solder block was placed between the base materials to be welded, fixed with a clamp, and then Nicobraz White Stop Off Type II solder resist alumina powder was applied to the outer surface of the sample to prevent solder loss during brazing; the sample was laser brazed with a laser power of 1400W, a laser scanning speed of 0.012m / s, a defocus of -0.8mm, an argon gas (99.99%) as the protective gas, and a gas flow rate of 23L / min.

[0047] Application Example 2

[0048] The brazing material block A2 prepared in Example 2 was used for brazing dissimilar metals, and the base materials to be welded were cemented carbide (WC-20Co) and titanium (TA2). The specific brazing method was the same as that in Application Example 1.

[0049] Application Example 3

[0050] The brazing material block A3 prepared in Example 3 was used for brazing dissimilar metals, and the base materials to be welded were cemented carbide (WC-20Co) and titanium (TA2). The specific brazing method was the same as that in Application Example 1.

[0051] The solder blocks in Application Examples 1-3 can all achieve soldering connection of dissimilar metals, among which Application Example 3 has the best soldering effect, and the wettability of the solder block is A3>A2>A1.

[0052] This specific implementation is only an explanation of the present invention, not a limitation of the present invention. Any changes made by those skilled in the art after reading the specification of the present invention will be protected by the patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A new type of cobalt-based solder, characterized in that: According to the weight percentage, the solder composition is: Co30-70%, Ni 14-27%, Cr 11-20%, Fe 3-6.5%, Mn 1-1.5%, Si 3-6%, B 2~4%, Sc 0.3~0.5%, Y 0.2~0.4%, and the balance are inevitable impurities.

2. The novel cobalt-based solder according to claim 1, characterized in that: According to the weight percentage, the solder composition is: Co 35%, Ni 27%, Cr 20%, Fe 6.5%, Mn 1.5%, Si 6%, B 3%, Sc 0.5%, Y 0.4%, and the balance being inevitable impurities.

3. The novel cobalt-based solder according to claim 1, characterized in that: Calculated by weight percentage, the solder comprises: Co 50%, Ni 20%, Cr 15%, Fe 6%, Mn 1%, Si 5%, B2%, Sc 0.5%, Y0.4%, and the remainder is inevitable impurities.

4. The novel cobalt-based solder according to claim 1, characterized in that: Calculated by weight percentage, the solder comprises: Co 65%, Ni 14%, Cr 11%, Fe 3%, Mn 1%, Si 3%, B2%, Sc 0.5%, Y0.4%, and the remainder is inevitable impurities.

5. The method for preparing the novel cobalt-based solder according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Batching: Weigh the raw materials of each component to be smelted according to the mass percentage of the solder; (2) Melting: The weighed raw materials are melted at high temperature in a high vacuum non-consumable arc melting furnace. After the melting is completed, the raw materials are cooled to room temperature and sampled to obtain an alloy ingot of the brazing material; (3) Cutting: Cut the alloy mother ingot into the required shape and size by wire cutting method.

6. The method for preparing the novel cobalt-based solder according to claim 5, characterized in that: In step (1), the raw materials of each component are particles with a purity greater than 99.99%.

7. The method for preparing the novel cobalt-based solder according to claim 5, characterized in that: In step (2), the non-consumable arc melting furnace is evacuated to below -4 Pa before smelting, and then filled with argon gas with a purity of 99.99% until the pressure reaches -0.05 MPa.

8. The method for preparing the novel cobalt-based solder according to claim 7, characterized in that: In step (2), the high temperature smelting process is: keep warm at 1500-1600°C for 3 min, keep warm at 1400-1500°C for 3 min, keep warm at 1300-1400°C for 3 min, during which the electromagnetic stirrer is turned on for stirring, the current is controlled at 400-600A, and pouring is performed at 1400°C.

9. Application of the novel cobalt-based solder according to any one of claims 1 to 4, characterized in that: The brazing filler metal is used for brazing connection of dissimilar high-temperature alloy materials such as cemented carbide and titanium or cemented carbide and steel, and the brazing temperature is 950°C to 1100°C.

10. The use of the novel cobalt-based solder according to claim 9, characterized in that: The brazing connection method is as follows: the brazing material is placed between two base materials to be welded, and after being fixed with a clamp, the sample is laser brazed, the laser power is 1400W, the laser scanning speed is 0.012m / s, the defocus amount is -0.8mm, the protective gas is argon, and the gas flow rate is 23L / min.

Citation Information

Patent Citations

  • Coating structure material

    CN104662201A

  • High-temperature-resistant multi-element high-entropy alloy brazing filler metal and preparation method

    CN117798547A

  • Solder alloy for repairing turbine blades contains chromium, nickel, silicon and a balance of cobalt

    DE102004018668A1

  • Cobalt-containing brazing alloys

    GB803253A

  • A cobalt-chromium base alloy

    GB809088A